Chest CT scan plus x-ray versus chest x-ray for the follow-up of completely resected non-small-cell lung cancer (IFCT-0302): a multicentre, open-label, randomised, phase 3 trial. Issue 9 (September 2022) - Westeel, Virginie; Foucher, Pascal; Scherpereel, Arnaud; Domas, Jean; Girard, Philippe; Trédaniel, Jean; Wislez, Marie; Dumont, Patrick; Quoix, Elisabeth; Raffy, Olivier; Braun, Denis; Derollez, Marc; et al.
Summary: Background: Even after resection of early-stage non-small-cell lung cancer (NSCLC), patients have a high risk of developing recurrence and second primary lung cancer. We aimed to assess efficacy of a follow-up approach including clinic visits, chest x-rays, chest CT scans, and fibre-optic bronchoscopy versus clinical visits and chest x-rays after surgery for resectable NSCLC. Methods: In this multicentre, open-label, randomised, phase 3 trial (IFCT-0302), patients aged 18 years or older and after complete resection of pathological stage I–IIIA NSCLC according to the sixth edition of the TNM classification were enrolled within 8 weeks of resection from 122 hospitals and tertiary centres in France. Patients were randomly assigned (1:1) to CT-based follow-up (clinic visits, chest x-rays, thoraco-abdominal CT scans, and fibre-optic bronchoscopy for non-adenocarcinoma histology) or minimal follow-up (visits and chest x-rays) after surgery for NSCLC, by means of a computer-generated sequence using the minimisation method. Procedures were repeated every 6 months for the first 2 years and yearly until 5 years. The primary endpoint was overall survival analysed in the intention-to-treat population. Secondary endpoints, also analysed in the intention-to-treat population, included disease-free survival. This trial is registered with ClinicalTrials.gov, NCT00198341, and is active, but not enrolling. Findings: Between Jan 3, 2005, and Nov 30, 2012, 1775 patients were enrolled and randomly assigned to a follow-up group (888 patients to the minimal follow-up group; 887 patients to the CT-based follow-up group). Median overall survival was not significantly different between follow-up groups (8·5 years [95% CI 7·4–9·6] in the minimal follow-up group vs 10·3 years [8·1–not reached] in the CT-based follow-up group; adjusted hazard ratio [HR] 0·95, 95% CI 0·83–1·10; log-rank p=0·49). Disease-free survival was not significantly different between follow-up groups (median not reached [95% CI not estimable–not estimable] in the minimal follow-up group vs 4·9 [4·3–not reached] in the CT-based follow-up group; adjusted HR 1·14, 95% CI 0·99–1·30; log-rank p=0·063). Recurrence was detected in 246 (27·7%) of 888 patients in the minimal follow-up group and in 289 (32·6%) patients of 887 in the CT-based follow-up group. Second primary lung cancer was diagnosed in 27 (3·0%) patients in the minimal follow-up group and 40 patients (4·5%) in the CT-based follow-up group. No serious adverse events related to the trial procedures were reported. Interpretation: The addition of thoracic CT scans during follow-up, which included clinic visits and chest x-rays after surgery, did not result in longer survival among patients with NSCLC. However, it did enable the detection of more cases of early recurrence and second primary lung cancer, which are more amenable to curative-intent treatment, supporting the use of CT-based follow-up, especially in countries where lung cancer screening is already implemented, alongside with other supportive measures. Funding: French Health Ministry, French National Cancer Institute, Weisbrem-Benenson Foundation, La Ligue Nationale Contre Le Cancer, and Lilly Oncology. Translation: For the French translation of the abstract see Supplementary Materials section.